Ternary composite ceramic material as well as preparation method and application thereof

By using ternary composite ceramic materials composed of silicon carbide, boron nitride and titanium diboride, the existing heating body materials have solved the problems of large temperature gradient and high cost under high temperature and high pressure conditions, and achieved efficient and stable heating performance, which is suitable for multi-sided top presses and other equipment.

CN119751079AActive Publication Date: 2025-04-04SUN YAT SEN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411983493.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing heating body materials have problems such as large temperature gradient, high cost, high process difficulty and poor chemical stability under high temperature conditions, which are difficult to meet the efficient heating needs of multi-sided top presses and other equipment.

Method used

The ternary composite ceramic material consisting of silicon carbide, boron nitride and titanium diboride is prepared through a sintering process to achieve stable heating of up to 20GPa and above 2000K.

Benefits of technology

It achieves excellent physical and chemical stability and thermal stability, has a small temperature gradient characteristic, can be adjusted with low cost and simple process, and is suitable as a high-temperature and high-pressure experimental resistance tube heating body in multi-sided top presses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751079A_ABST
    Figure CN119751079A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary composite ceramic material as well as a preparation method and application thereof. The ternary composite ceramic material is obtained by sintering raw materials including silicon carbide, boron nitride and titanium diboride. Through the mass ratio of silicon carbide, boron nitride and titanium diboride in the ternary composite ceramic material, the prepared ternary composite ceramic material realizes stable heating up to 20GPa and more than 2000K, and shows excellent physical and chemical stability and thermal stability and small temperature gradient characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and more specifically, relates to a ternary composite ceramic material and a preparation method and application thereof. Background Art

[0002] The large cavity press device originated from the high-pressure technology developed in the early 20th century, including the two-sided top press and the polyhedron pressure chamber device. The large cavity press is widely used in high-temperature and high-pressure experiments in physics, chemistry, materials, geology and other disciplines due to its precise control of temperature and pressure. It is often used in the study of the synthesis, transformation and physical and chemical properties of materials under extreme conditions. In addition, it is also the main equipment for synthesizing superhard materials such as diamond and cubic boron nitride (cBN) in China. The large cavity press uses resistive heating to maintain a high temperature environment under high pressure conditions. The heating process of the sample in the cavity needs to be achieved through a heating body made of special materials, so the heating body plays a vital role in the heating process.

[0003] Common heating bodies at this stage include: rhenium (Re), graphite, titanium carbide (TiC)-based composite materials, doped LaCrO3, EBN, etc. Among them, Re is applicable to a very wide range of temperature and pressure, but the main problem is that it is expensive and easy to oxidize and deteriorate at high temperature for a long time, and the temperature gradient is large. The temperature distribution of graphite heating bodies is uniform, the performance is stable, and the price is low, but it is corrosive to tungsten carbide anvils, has poor heat storage, low physical and chemical stability, and transforms into diamond at higher temperature and pressure, losing the conductive heating performance, and the scope of application is limited. TiC-based composite materials have both chemical inertness and thermal stability. By adjusting the resistance, they can be used as X-ray transparent heating bodies. They are an important hotspot in the research of heating body materials, but the traditional preparation process is difficult to meet the application requirements. The commonly used polymer degradation process is complicated and easy to introduce impurities. Boron-doped diamond is also a hotspot in the research of heating bodies. This kind of heating body has excellent performance, but the heating body material itself needs to be prepared under harsh high temperature and high pressure conditions, which is costly and difficult to process. LaCrO3 heaters have uniform temperature distribution, good heating stability and corrosion resistance at high temperature and pressure up to 2700K, but they are difficult to process and shape, and the high conductivity activation energy makes it difficult to start heating. High oxygen fugacity at high temperature can easily change the valence state of the sample. Xia Tao and other researchers from Sun Yat-sen University have modified LaCrO3 by doping, solving most of the problems of LaCrO3 heaters except oxygen fugacity, improving the problem of conductivity activation energy to a certain extent, and pushing LaCrO3 heaters to a wider range of application prospects. However, while chemical space doping improves conductivity, it also reduces the melting point and environmental compatibility of the heater at high temperature. The temperature limit under high pressure is around 2000K.

[0004] Titanium boride (TiB2) has the advantages of high melting point, high hardness, low thermal expansion coefficient, good oxidation resistance and excellent chemical stability, and is suitable for many high-temperature environments. Hexagonal boron nitride (h-BN) has excellent properties such as low density, high melting point, strong chemical inertness, good heat resistance, insulation and machinability, but due to its graphite layered structure and poor sintering performance, h-BN is difficult to sinter densely. Mixing the two into a TiB2-h-BN composite material can combine the advantages of both parties, complement each other, and not only significantly improve densification, but also achieve adjustable mechanical properties and conductivity.

[0005] The EBN composite material (made of TiB2, AlN and BN) provided by Denka Corporation of Japan is also a commercial heating material that is transparent to X-rays. After being processed by the user, it has a lower operating current than graphite under high temperature and high pressure, and is a competitive substitute in the market. However, it will slightly corrode the WC anvil at high temperature, and the temperature rise range is limited (below 2000K). Summary of the invention

[0006] In view of the above existing technical problems, the primary purpose of the present invention is to provide a ternary composite ceramic material that achieves stable heating up to 20 GPa and above 2000 K, exhibits excellent physical and chemical stability and thermal stability, and has a small temperature gradient characteristic.

[0007] The second object of the present invention is to provide a method for preparing a ternary composite ceramic material.

[0008] The third object of the present invention is to provide an application of a ternary composite ceramic material in the preparation of a heating body material.

[0009] The fourth object of the present invention is to provide a ternary composite ceramic material for use as a heating body material in a multi-faceted top press.

[0010] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0011] The present invention claims protection for a ternary composite ceramic material obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. Calculated by mass percentage, the raw materials include: 25-35% silicon carbide, 5-15% boron nitride, and 55-65% titanium diboride.

[0012] The present invention claims protection for a ternary composite ceramic material obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. Calculated by mass percentage, the raw materials include: 8-12% silicon carbide, 8-32% boron nitride and 58-82% titanium diboride.

[0013] The present invention claims protection for a ternary composite ceramic material obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. Calculated by mass percentage, the raw materials include: 18-22% silicon carbide, 8-22% boron nitride and 58-72% titanium diboride.

[0014] The present invention introduces SiC into the TiB2-h-BN binary system material and controls the content ratio of each component to develop a ternary composite ceramic material with excellent performance, which can be stably heated at up to 20GPa and above 2000K, showing excellent physical and chemical stability and thermal stability as well as small temperature gradient characteristics. It can ensure the stability of the composition of the required heated sample, has excellent thermal stability and physical and chemical stability as well as heat storage performance under high pressure, and can achieve the difficult uniform temperature field heating experimental task under wide temperature and pressure conditions.

[0015] The ternary ceramic composite material has moderate resistance and low conductivity activation energy, and can be used universally in a wide temperature range and pressure range. The ternary composite material has excellent processing performance, low cost, simple production, and X-ray transparency, and is suitable as an experimental resistance tube heater.

[0016] The inventors have discovered through research that the mass proportion of each component in the above-mentioned ternary composite ceramic material is very important. When the silicon carbide content in the ternary composite ceramic material increases or decreases, or the boron nitride content increases or decreases, it is difficult to heat stably above 1273K.

[0017] The raw material cost of the present invention is low and easy to obtain, and no special preparation is required. The ternary composite ceramic material realizes adjustable resistance, ensures a low working current, has low requirements for working cables, and broadens the scope of application. In addition, after adding SiC, the sample can be compactly formed and sintered only by pressing the tablet press, which solves the problem of poor machining performance of TiB2 and h-BN, and is convenient for storage, transportation and reprocessing.

[0018] Furthermore, the present invention seeks to protect a method for preparing a ternary composite ceramic material, comprising pressurizing a mixture of silicon carbide, boron nitride, titanium diboride, and a curing agent, heating and curing, and sintering at 1100-1300° C. in an inert atmosphere to obtain the ternary composite ceramic material.

[0019] The present invention solidifies the mixed raw materials at low temperature and then sinters them in a normal pressure atmosphere to finally prepare a ternary composite ceramic material. The method has the advantages of fast production speed, high yield, no pollution emission in the whole process, and no special requirements for the performance of process equipment. The preparation method has no impurity removal step, does not involve laser, discharge, precursor conversion and other processes, and can be completed using the most common oven and atmosphere sintering furnace in the industry.

[0020] Preferably, the curing agent is selected from one or more of phenolic resin liquid paraffin, polyethylene butyl, and polyethylene glycol. Further preferably, the curing agent is phenolic resin.

[0021] Preferably, the heating temperature is 150-250°C. More preferably, the heating temperature is 185-195°C.

[0022] Preferably, the sintering time is 5-15 hours.

[0023] Preferably, the boron nitride is selected from one or more of hexagonal boron nitride (h-BN), rhombohedral boron nitride (RBN) or wurtzite boron nitride (WBN).

[0024] Preferably, the inert atmosphere includes one or both of nitrogen and argon.

[0025] Furthermore, the present invention seeks to protect the use of a ternary composite ceramic material in the preparation of a heating body material.

[0026] Furthermore, the present invention claims protection for the use of a ternary composite ceramic material as a heating body material in a multi-faceted top press, and is particularly suitable for use as a high-temperature and high-pressure experimental resistance tube heating body in a multi-faceted top press.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a ternary composite ceramic material, which achieves stable heating up to 20 GPa and above 2000 K, and exhibits excellent physical and chemical stability and thermal stability as well as a small temperature gradient characteristic. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of two standard specifications of the finished heating body prepared in Example 1 and the matching electrodes with the same composition.

[0030] Figure 2 This is the X-ray powder diffraction pattern of the ternary composite ceramic material prepared in Example 1.

[0031] Figure 3 Schematic diagram of the heating body sample loading method.

[0032] Figure 4 This is the heating performance phase diagram of the heating body tested at 3 GPa.

[0033] Figure 5 This is the power-temperature curve of the high-temperature and high-pressure test of the heating body prepared in Example 1.

[0034] Figure 6This is the temperature-resistance curve of the high temperature and high pressure test of the heating body prepared in Example 1.

[0035] Figure 7 The heating body prepared in Example 1 was subjected to heating-cooling-heating tests at 5 GPa and 7 GPa.

[0036] Figure 8 These are the thermal power-temperature curve and temperature-heating resistance curve of the heating body under 22 GPa and 2100 K conditions.

[0037] Fig. 9 The figures are the heating power-temperature curves and the temperature-heating resistance curves of the embodiments and comparative examples except embodiment 1.

[0038] Fig.10 This is the test result of the heating element prepared by using the formula provided in patent CN 113698210A as raw materials in comparative example 11. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0040] The raw materials used in the examples and comparative examples of the present invention are as follows.

[0041] TiB2, 99.99%, 1um, Guangzhou Metal Metallurgical Group Co., Ltd.

[0042] SiC, 99.9%, 1-2um, Shanghai McLean Biochemical Technology Co., Ltd.

[0043] h-BN, 99.9%, metal basis, 1-2um, Shanghai McLean Biochemical Technology Co., Ltd.

[0044] Example 1

[0045] Silicon carbide 30%, boron nitride 10%, titanium diboride 60% by mass percentage were mixed into powder, 100 μL / g phenolic resin was added, and the mixture was transferred into a mold (customized according to the required heating body size, and the mold size does not affect the preparation effect). The mixture was pressed and formed under a tablet press at a pressure of 2 MPa, heated to 190°C for curing, and sintered at 1300°C for 10 hours under argon to obtain a heating body, i.e., a ternary composite ceramic material, which was recorded as TBSB-631. The appearance of the heating body prepared in Example 1 is as follows: Figure 1 As shown, different molds can be used for pressing according to different needs, or the sintered blocks can be cut according to needs.

[0046] Embodiment 2-6

[0047] The differences between Examples 2-6 and Example 1 are:

[0048] Embodiment 2: Silicon carbide 10%, boron nitride 10%, and titanium diboride 80% are mixed into powder according to the mass percentage.

[0049] Embodiment 3: Silicon carbide 10%, boron nitride 20%, and titanium diboride 70% are mixed into powder according to the mass percentage.

[0050] Embodiment 4: Silicon carbide 10%, boron nitride 30%, and titanium diboride 60% are mixed into powder according to the mass percentage.

[0051] Embodiment 5: Silicon carbide 20%, boron nitride 10%, and titanium diboride 70% are mixed into powder according to the mass percentage.

[0052] Embodiment 6: 20% silicon carbide, 20% boron nitride and 60% titanium diboride are mixed into powder according to the mass percentage.

[0053] Comparative Examples 1-11

[0054] The differences between Comparative Examples 1-11 and Example 1 are:

[0055] Comparative Example 1: Silicon carbide 0%, boron nitride 0%, and titanium diboride 100% were mixed into powder according to the mass percentage.

[0056] Comparative Example 2: Silicon carbide 0%, boron nitride 10%, and titanium diboride 90% were mixed into powder according to the mass percentage.

[0057] Comparative Example 3: Silicon carbide 0%, boron nitride 20%, and titanium diboride 80% were mixed into powder according to the mass percentage.

[0058] Comparative Example 4: Silicon carbide 10%, boron nitride 0%, and titanium diboride 90% were mixed into powder according to the mass percentage.

[0059] Comparative Example 5: 20% silicon carbide, 30% boron nitride and 50% titanium diboride were mixed into powder according to the mass percentage.

[0060] Comparative Example 6: 30% silicon carbide, 20% boron nitride and 50% titanium diboride were mixed into powder according to the mass percentage.

[0061] Comparative Example 7: 30% silicon carbide, 30% boron nitride and 40% titanium diboride were mixed into powder according to the mass percentage.

[0062] Comparative Example 8: 30% silicon carbide, 0% boron nitride and 70% titanium diboride were mixed into powder according to the mass percentage.

[0063] Comparative Example 9: Silicon carbide 0%, boron nitride 30%, and titanium diboride 70% were mixed into powder according to the mass percentage.

[0064] Comparative Example 10: 20% silicon carbide, 0% boron nitride and 80% titanium diboride were mixed into powder according to the mass percentage.

[0065] Comparative Example 11: According to the ratio given in Patent Publication No. CN 113698210A: 3% silicon carbide, 72% boron nitride, and 25% titanium diboride, mixed into powder.

[0066] Test Example 1

[0067] Figure 2 This is the X-ray powder diffraction pattern of the ternary composite ceramic material. Figure 2 It can be seen that the ternary composite ceramic material is a TiB2-SiC-BN structure containing trace impurities. It is speculated that the impurities come from a small amount of oxygen mixed in the argon gas, and the high-temperature reaction of the binder and the raw materials.

[0068] Test Example 2

[0069] Test method: The heating performance of the heating body prepared in the embodiment and the comparative example was tested at 3 GPa using a Walker type multi-faceted top press. Figure 3 The sample loading method shown in the figure is to put the sample into the cavity of the large cavity press for ultra-high temperature and high pressure heating performance test. The high pressure and high temperature environment are provided by the six-sided top anvil controlled by the hydraulic system and the resistive heating method respectively. The performance graph is drawn by summarizing the change rules of the pressure, temperature, power, resistance and other data obtained in the heating data of the test.

[0070] Figure 4 This is the heating performance phase diagram of the heating body tested at 3 GPa. Figure 4 In the figure, the gray cross means that the sample resistance exceeds the range, and the test data cannot be obtained and cannot be applied. The green circle means that the sample can obtain ultra-high temperature and high pressure heating data through the test, so there is a certain applicable temperature range (its high temperature limit is below 1400K, see test example 6 / Fig. 9 ). The five-pointed star represents the sample with the best heating data. The heating temperature range tested under 3GPa pressure is the widest (0-1467K), which exceeds other embodiments and comparative examples under the same conditions (<1400K). Therefore, it is the most suitable material for the required application scenario.

[0071] Test Example 3

[0072] The high temperature and high pressure application of the heating body prepared in Example 1 was tested by a Walker-type multi-faceted top press. The pressure range was 3-20 GPa. The heating rate of the sample in the cavity can be freely set. The test examples in this article were all set to 150 K / min. The temperature detection used a thermocouple wire made of C-type W / Re alloy or R-type Pt / Rh. The detection range was 0-2500 K. A tungsten carbide anvil was used, and the pressure transmission medium was an octahedron made of ARMC-646 or 584 powder.

[0073] Figure 5 The heating body prepared in Example 1 was tested under high pressure of 3-7 GPa and the heating temperature can be stably increased to 2000K. Figure 5 (d) shows that the performance of the heating body hardly changes after the first round of heating after three consecutive heating experiments.

[0074] Figure 6 The high-pressure resistance test results of the heater prepared in Example 1 at 3-7 GPa are shown. The heaters under different pressures show similar resistance change trends as the temperature increases, and both show a turning point at 900-1100 K, while the temperature of the resistance turning point increases with the applied pressure. Figure 6 (d) is a three-time continuous heating experiment, i.e., after each heating reaches the highest power point, the heating power is immediately reduced to 0 W for natural annealing. The annealing speed is variable, about 800 K / min. The temperature detection shows that the next heating starts immediately after the temperature drops to 323 K. The analysis results show that the turning point disappears after the first heating and the resistance value tends to be stable.

[0075] Test Example 4

[0076] The test method is basically the same as the above one, except that the performance test is changed from a single heating test to a heating-annealing-heating test. The pressures applied to the samples are 5 GPa and 7 GPa, respectively, and the corresponding heating temperatures are 1400 K and 1970 K, respectively. The annealing is water-cooled annealing, and the cooling rate can be set freely. In this test, it is set to 100 K / min. The second heating is started immediately after the temperature detection shows that it has dropped to 323 K.

[0077] Figure 7 The figure shows the heating-annealing-heating test of TBSB-631 heaters of different specifications under different pressures. Although there will be more or less position and resistance deviations in each loading, Figure 7 The data shown and Figure 5 d. Figure 6There is no significant difference in the results of multiple heating cycle experiments shown in d. The resistance curves of different heaters show similar trends during the test, including the upper limit of heating, the stable correspondence between heating power and heating temperature, the sharp drop and slow rise of resistance with increasing temperature, and the disappearance of the resistance turning point. This proves the repeatability of the heating experiment and the stability of the heater resistance in various heating tests.

[0078] Therefore, the heating element prepared in Example 1 exhibits good heating performance and stability under high temperature and high pressure tests, and is a high-performance heating element with excellent application value and wide applicability.

[0079] Test Example 5

[0080] The test method is the same as that of Test Example 3, except that: (1) Cr2O3 (5wt%) doped MgO is used as the pressure medium instead of ARMC 646; (2) In order to reduce the force-bearing area and achieve a higher pressure, a smaller cylindrical resistance tube heater with an outer diameter of 2.5mm, an inner diameter of 1.6mm, and a length of 5-6mm is prepared by a fine process; (3) In order to achieve a better thermal insulation effect and protect the heater, the exposed surface of the external electrode of the heater is covered with a Re metal sheet with a thickness of 0.85mm.

[0081] Figure 8 The thermal power-temperature curve and temperature-heating resistance curve of the heating body under 22GPa and 2100K conditions are shown in the following table. Figure 8 As shown in the figure, the excellent heating performance of stable heating to 2100K at ultra-high pressure above 20GPa is achieved, which greatly broadens the application pressure range of the heating body. At the same time, under ultra-high pressure, the heating power and heating temperature of the heating body still maintain an approximately linear correlation, and the resistance change trend is similar to the above test example, which means that at pressures above 20GPa, its physical and chemical properties at high temperatures have not changed significantly, and it is a reliable and practical heating body material.

[0082] Test Example 6

[0083] The test method refers to the test method of Test Example 2.

[0084] Fig. 9 The heating power-temperature curves and the temperature-heating resistance curves of each embodiment and comparative example except embodiment 1 are shown in FIG. Fig. 9 a, c, and e are heating power-temperature curves of various embodiments and comparative examples except embodiment 1; Fig. 9 Figures b, d, and f are temperature-heating resistance curves of each embodiment and comparative example except embodiment 1.

[0085] Fig. 9TBSB-730 corresponds to Example 8, TBSB-703 corresponds to Example 9, TBSB-802 corresponds to Example 10, TBSB-712 corresponds to Example 3, TBSB-721 corresponds to Example 5, TBSB-622 corresponds to Example 6, TBSB-613 corresponds to Example 4, and TBSB-811 corresponds to Example 2. Figure 4 The material prepared in the comparative example corresponding to the cross in the figure cannot be subjected to heating test because its resistance exceeds the measurement range, and no meaningful performance curve can be obtained, so it is not considered.

[0086] In general, other comparative examples and embodiments also have certain application potential in the field of ultra-high temperature and high pressure, but the upper limit of the heating temperature of the comparative examples is significantly lower and can only be used for medium and low temperature heating. The embodiments other than Example 1 have shown heating performance with certain value (the upper limit of the temperature rise is higher than 1273K under a pressure of 3GPa), but their performance is slightly inferior to that of the heating body prepared in Example 1.

[0087] Test Example 7

[0088] The test method of comparative example 11 is exactly the same as that of test example 2, except that it cannot heat up and has no temperature and heating resistance data, so the voltage-power data that has exceeded the range is displayed.

[0089] like Fig.10 As shown, it was found that the material was almost difficult to conduct electricity, the working power was extremely low, the working voltage was extremely high, and it was impossible to be heated as a resistance tube. Therefore, it could not be used as a raw material for heating elements.

[0090] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A ternary composite ceramic material, characterized in that: The invention is obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. According to mass percentage, the raw materials include: 25-35% silicon carbide, 5-15% boron nitride and 55-65% titanium diboride.

2. A ternary composite ceramic material, characterized in that: The invention is obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. According to mass percentage, the raw materials include: 8-12% silicon carbide, 8-32% boron nitride and 58-82% titanium diboride.

3. A ternary composite ceramic material, characterized in that: The invention is obtained by sintering raw materials of silicon carbide, boron nitride and titanium diboride. According to mass percentage, the raw materials include: 18-22% silicon carbide, 8-22% boron nitride and 58-72% titanium diboride.

4. The method for preparing the ternary composite ceramic material according to any one of claims 1 to 3, characterized in that: The mixture of silicon carbide, boron nitride, titanium diboride and a curing agent is pressurized, heated and cured, and sintered at 1100-1300° C. in an inert atmosphere to obtain the ternary composite ceramic material.

5. The preparation method according to claim 4, characterized in that: The curing agent is selected from one or more of phenolic resin liquid paraffin, polyethylene butyl and polyethylene glycol.

6. The preparation method according to claim 4, characterized in that: The temperature of the heating curing is 150-250°C.

7. The preparation method according to claim 4, characterized in that: The sintering time is 5-15h.

8. The preparation method according to claim 4, characterized in that: The boron nitride is one or more of hexagonal boron nitride, rhombohedral boron nitride or wurtzite boron nitride.

9. Use of the ternary composite ceramic material according to any one of claims 1 to 3 in the preparation of heating body materials.

10. Use of the ternary composite ceramic material according to any one of claims 1 to 3 as a heating body material in a multi-faceted top press.

Citation Information

Patent Citations

  • Technology for preparing high-strength electric conducting ceramic of titanium-carbon biboride

    CN1058577A

  • Titanium diboride-boron nitride-silicon carbide ceramic composite material prepared by hot pressed sintering and preparation method thereof

    CN113698210A

  • Ceramic sintered compact, method of manufacturing the same and exothermic element for vaporization of metal

    JP2007254181A